2022
DOI: 10.3389/fchem.2022.861288
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Fused Pyrimidine Systems as EGFR Inhibitors and Their Structure–Activity Relationship

Abstract: Epidermal growth factor receptor (EGFR) belongs to the family of tyrosine kinase that is activated when a specific ligand binds to it. The EGFR plays a vital role in the cellular proliferation process, differentiation, and apoptosis. In the case of cancer, EGFR undergoes uncontrolled auto-phosphorylation that results in increased cellular proliferation and decreased apoptosis, causing cancer promotion. From the literature, it shows that pyrimidine is one of the most commonly studied heterocycles for its antipr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 133 publications
0
9
0
Order By: Relevance
“…As the incorporation of a solubilizing functional group in compounds 31 and 32 lowered its EGFR kinase inhibition activity and failed to impart cellular potency, we used molecular docking studies to identify a site capable of bearing a solubilizing group without that group also affecting the EGFR kinase enzyme inhibitory activity. Osimertinib (6) was docked onto the crystal structure of DBPR112 (11) and their binding orientation in the EGFR protein was compared (Figure 2). It was found that the Michael acceptor group of 6 was placed near the Cys797 residue, similar to 11.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the incorporation of a solubilizing functional group in compounds 31 and 32 lowered its EGFR kinase inhibition activity and failed to impart cellular potency, we used molecular docking studies to identify a site capable of bearing a solubilizing group without that group also affecting the EGFR kinase enzyme inhibitory activity. Osimertinib (6) was docked onto the crystal structure of DBPR112 (11) and their binding orientation in the EGFR protein was compared (Figure 2). It was found that the Michael acceptor group of 6 was placed near the Cys797 residue, similar to 11.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Lung cancer is one of the leading causes of cancer deaths worldwide, accounting for a quarter of all cancer deaths. , Most lung cancer patients, around 80–85%, have the non-small cell lung cancer (NSCLC) disease, which is characterized by somatic epidermal growth factor receptor (EGFR) activating mutations in 10–15% of Caucasian and 30–50% of Asian patients. , Several drugs targeting mutated EGFR have been approved, such as the first-generation EGFR inhibitors gefitinib ( 1 ) and erlotinib ( 2 ), which were approved by the US FDA in 2003 and 2004 (Figure ). Gefitinib and erlotinib effectively target the EGFR exon 19 deletion or exon 21 L858R single point mutation , and most patients respond well, but about half of them develop resistance due to a secondary T790M gatekeeper mutation. , Several second-generation EGFR inhibitors capable of overcoming resistance due to T790M mutations have also been approved, including afatinib ( 3 ), dacomitinib ( 4 ), and ceritinib ( 5 ). These second-generation inhibitors all bear a Michael acceptor warhead that forms an irreversible covalent bond with the cysteine residue (Cys797) in the active site of EGFR …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present research, we studied the relationship between Among all of the identified genes, the EGFR belongs to a family of tyrosine kinases that are activated when specific ligands bind to them. 29,30 EGFR plays a crucial role in the cell proliferation process, differentiation and apoptosis. 30 In the case of cancer, EGFR undergoes uncontrolled autophosphorylation, leading to increased cell proliferation and decreased apoptosis, which results in cancer promotion.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrimidine and its fused derivatives are a class of heterocyclic scaffolds with biological and pharmacological activities [16][17][18][19][20][21][22][23][24][25] including anticancer [16][17][18], antihypertensive [19], anxiolytic, antioxidant [16], antiviral, antifungal [20][21][22], anti-inflammatory [23], analgesic activities [23], and antibacterial [21,22] properties. These compounds hold a unique place in the field of biological and medicinal chemistry, inspiring researchers to create novel motifs with modified structures [26,27]. In the framework of our current research interest in carboncarbon bond-forming reactions [28][29][30][31][32][33][34][35] including Hantzsch reactions [15,[36][37][38], Michael addition [34,36,[39][40][41][42][43], Biginelli-like reaction [10,11,…”
Section: Introductionmentioning
confidence: 99%